Exploring English for Academic Purposes Program: Needs analysis and impact evaluation - Damayanti, Ika Lestari; Derinalp, Pelin; Asyifa, Firly; Suryatama, Kurniawan (Studies in English Language and Education, 2024)
A collaborative project involving two universities was initiated to support lecturers in Indonesia in designing English for Academic Purposes (EAP) instruction adjusted to local needs and the latest advancements in EAP. Using a mixed-methods approach and developmental research design, the study included a needs analysis, implementation of an EAP professional learning program, and a program evaluation survey. Needs analysis was conducted through a survey with 88 lecturers and 618 students from 41 universities in Indonesia. The results of the need analysis were then used to inform the design and delivery of an online professional development program for EAP lecturers. Based on the needs analysis results, the EAP lecturers who participated in the survey conveyed that they required improvements in digital skills, teaching techniques for diverse proficiency levels, and methods for improving students productive skills and critical thinking abilities. The participating students also expressed their need for interactive EAP activities, team-based learning, and the use of social media for collaboration and connectivity. Informed by the needs analysis results, a two-month program was designed and delivered in eight 90-minute video conferences, combined with asynchronous activities on a learning platform. As revealed in the post-program survey, the participating lecturers feedback on the program highlighted contributing factors to the changes in their technological and pedagogical content knowledge, particularly in the areas of using digital tools and differentiated instruction in EAP. This study highlights the need for continuous professional development to enhance EAP lecturers ability to effectively apply acquired skills in teaching and professional practice.